Constructive Communication Patterns of Students in Facing Psychological Pressure in Completing Final Projects - Achmad Irfan Muzni; Awang Setiawan Wicaksono (Psikologia : Jurnal Psikologi, 2015)
Generally most students are feeling tense and depressed in finishing the final project. This condition if it doesn’t proportionately respond it will cause severe reactions such as depression feeling that will make them can’t complete their studies. This research is aiming to obtain a precise pattern of constructive communication among students in order to maintain the spirit when they faced psychological pressure while completing the final project. This study was matching methods approach which conducted at higher education institutions in Gresik. The subjects were the students who are taking the final project. Data collection did by Report Cards Card System, depth interviews and Focus Group Discussion. The data was analyzed by triangulation method. Research found in facing of psychological distress, students develop social communication patterns by opening discussion forum, telling the problem directly, asking for technical assistance, keeping and grumbling the problems and isolate their self. The constructive communication patterns that can be developed by students is providing mutual support group, sharing experiences, maintaining communication with the supervisor, discussing the issues, asking each other’s progress, and pulling away to reduce the exchange of information in order to maintain concentration in finishing the final project.